2018
DOI: 10.13057/biodiv/d200120
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between environmental parameters and the plankton community of the Batuhideung Fishing Grounds,

Abstract: Takarina ND, Nurliansyah W, Wardhana W. 2019. Relationship between environmental parameters and the planktoncommunity of the Batuhideung Fishing Grounds, Pandeglang, Banten, Indonesia. Biodiversitas 20: 171-180. Phytoplankton has a roleas primary producers and zooplankton as primary consumers in the marine environments. The composition of the plankton communityis dependent on the physical and chemical characteristics of the waters. The aim of the research described here was to analyze thecommunity structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…This can be seen in Tables 6 and 7 that both the spatial and temporal parameters of salinity consistently exert influence on the abundance of zooplankton. This is according to the research of Almeida et al (2012), Jeyaraj et al (2014), and Takarina et al (2019) which shows the effect of salinity on the distribution and abundance of zooplankton in waters.…”
Section: The Relationship Of Environmental Conditions With the Planktmentioning
confidence: 70%
See 3 more Smart Citations
“…This can be seen in Tables 6 and 7 that both the spatial and temporal parameters of salinity consistently exert influence on the abundance of zooplankton. This is according to the research of Almeida et al (2012), Jeyaraj et al (2014), and Takarina et al (2019) which shows the effect of salinity on the distribution and abundance of zooplankton in waters.…”
Section: The Relationship Of Environmental Conditions With the Planktmentioning
confidence: 70%
“…Waya et al (2017) found that transparency significant effect on the abundance of plankton in the lake Lake Victoria, Tanzania. Furthermore, Takarina et al (2019) also found a strong relationship between phytoplankton and the intensity of sunlight and nutrients in the coastal waters of Banten. Thus, both the tides and ebb abundance of phytoplankton are influenced by the presence of sunlight and nutrients.…”
Section: The Relationship Of Environmental Conditions With the Planktmentioning
confidence: 84%
See 2 more Smart Citations
“…The Indonesian Throughflow makes the distribution of oceanographic parameters very dynamic (Gordon 2005). Even with very dynamic fluctuations of SST and SSC in the waters, it results in alternating upwelling and downwelling events (Atmadipoera and Widyastuti 2015;Sari et al 2018;Wijaya et al 2020) and has the potential to cause biological responses in water (Iskandar et al 2017;Takarina et al 2019). The distribution of skipjack tuna in the waters correlates to the thermal front location, not far from the…”
Section: Discussionmentioning
confidence: 99%